Piezo and pyroelectric radiation dosimetry - Augusto de Carvalho, Aparecido [UNESP]; Mascarenhas, Sergio [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1992)
The authors review the use of photoacoustic and pyroelectric radiation dosimeters. They compare the characteristics and results obtained with a photoacoustic radiation dosimeter (PARD) and a pyroelectric radiation dosimeter (PERD). The PARD and the PERD can be used to measure the energy fluence rate of continuous X-ray beams. In the same way, the single-pulse photoacoustic radiation dosimeter and the single-pulse pyroelectric radiation dosimeter (PPERD) were compared. They can measure the energy fluence of a single pulse of X-radiation. A theoretical model to explain the results obtained with the PPERD is presented and compared with experimental results.
Keywords: Dosimetry; Piezoelectricity; Pyroelectricity; Photoacoustic radiation dosimeters; Pyroelectric radiation dosimeters; Dosimeters